2022
DOI: 10.11648/j.jeece.20220702.12
|View full text |Cite
|
Sign up to set email alerts
|

Development of Solar Photo-Fenton Process for the Removal of Color, COD, and Turbidity from Institutional Wastewater

Abstract: In recent years, hard research has been aimed to develop effective technology for the treatment of wastewater and industrial effluent containing organic/inorganic contaminants. Amongst several technologies, the advanced oxidation processes (AOPs) recently have played a major role in the treatment of wastewater. In this study, the treatment of institutional wastewater by solar-photo-Fenton (UV/Fe 2+ /H 2 O 2 ) process based on AOPs was examined in terms of % color, % turbidity, and % COD removal. The solar-UV/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was found that a high removal efficiency was achieved, reaching 89% and 96%, respectively, in just 8 min. Arka et al (2021) [39] investigated the solar photo-Fenton method for the treatment of institutional wastewater. According to the study, the solar UV/Fe 2+ /H 2 O 2 process was very efficient in treating the wastewater from institutions, achieving a greater pollutant removal rate.…”
Section: Solar Photo-fenton Processmentioning
confidence: 99%
“…It was found that a high removal efficiency was achieved, reaching 89% and 96%, respectively, in just 8 min. Arka et al (2021) [39] investigated the solar photo-Fenton method for the treatment of institutional wastewater. According to the study, the solar UV/Fe 2+ /H 2 O 2 process was very efficient in treating the wastewater from institutions, achieving a greater pollutant removal rate.…”
Section: Solar Photo-fenton Processmentioning
confidence: 99%
“…The advanced Oxidation Processes (AOPs) could be quite effective for the degradation of persistent contaminants. Their efficiency is based on the generation of highly reactive OHradicals, which are capable of oxidizing many organic compounds (Arka et al, 2022). OHradicals are generated by the intervention of sunlight or other energy sources and are characterized by their great effectiveness in oxidizing organic matter (Litter, 2005) The versatility of AOPs lies in the different existing ways of producing free radicals, such as heterogeneous photocatalytic ozonation, anodic oxidation, ultraviolet/hydrogen peroxide (UV/H2O2), Fenton and Photo-Fenton, among others (Cruz-Gonzalez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%